2023
DOI: 10.3390/s23218915
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free SERS and MD Analysis of Biomarkers for Rapid Point-of-Care Sensors Detecting Head and Neck Cancer and Infections

Edoardo Farnesi,
Silvia Rinaldi,
Chen Liu
et al.

Abstract: For the progress of point-of-care medicine, where individual health status can be easily and quickly monitored using a handheld sensor, saliva serves as one of the best-suited body fluids thanks to its availability and abundance of physiological indicators. Salivary biomarkers, combined with rapid and highly sensitive detection tools, may pave the way to new real-time health monitoring and personalized preventative therapy branches using saliva as a target matrix. Saliva is increasing in importance in liquid b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Raman spectroscopy and micro spectroscopy are widely used for real-time cancer diagnostics to identify cancer tissues in the surgical room . The relative intensities of various body fluids such as serum, urine, and saliva were compared to reveal specific biomolecules related to DNAs (DNAs)/ribonucleic acids (RNAs), proteins, sugars, and lipids to diagnose cancer with label-free SERS substrates. , Numerous studies have reported the use of label-free SERS-based biosensors to diagnose breast, , prostate, , lung, , and other cancer. ,,,, The rate of protein breakdown is reduced in cancer patients, accumulating phenylalanine and its metabolites in the body. Therefore, bands associated with enzyme activity have a higher intensity than those of the normal group, while the bands with an abnormality in base metabolism resulting in reduced amino acid and sugar contents have lower intensity than those of the normal group. , l -tyrosine at ∼639 cm –1 is an important biomarker to distinguish cancer from healthy controls.…”
Section: Label-free Sers Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectroscopy and micro spectroscopy are widely used for real-time cancer diagnostics to identify cancer tissues in the surgical room . The relative intensities of various body fluids such as serum, urine, and saliva were compared to reveal specific biomolecules related to DNAs (DNAs)/ribonucleic acids (RNAs), proteins, sugars, and lipids to diagnose cancer with label-free SERS substrates. , Numerous studies have reported the use of label-free SERS-based biosensors to diagnose breast, , prostate, , lung, , and other cancer. ,,,, The rate of protein breakdown is reduced in cancer patients, accumulating phenylalanine and its metabolites in the body. Therefore, bands associated with enzyme activity have a higher intensity than those of the normal group, while the bands with an abnormality in base metabolism resulting in reduced amino acid and sugar contents have lower intensity than those of the normal group. , l -tyrosine at ∼639 cm –1 is an important biomarker to distinguish cancer from healthy controls.…”
Section: Label-free Sers Detectionmentioning
confidence: 99%
“…Saliva is important in liquid biopsy, which is a noninvasive approach that helps physicians diagnose and characterize specific diseases in patients and is considered an ideal body fluid owing to its accessibility and rich physiological markers. Farnesi et al validated the traceability of two salivary markers interleukin-8 and lysozyme associated with oropharyngeal squamous cell carcinoma and oral infection. The probable contact of the long side chain of lysozyme with the Ag surface is indicated by prominent bands in the SERS spectra: CC/CN stretching (885 cm –1 ), CH 2 wagging (1273 cm –1 ), and CH 2 scissoring (1460 cm –1 ).…”
Section: Label-free Sers Detectionmentioning
confidence: 99%